Impact of partial enzymatic hydrolysis on the transport and uptake of SPI nanoparticles post-digestion - Ling Chen; Yuan Lv; Xiaoyong Wang; Maoshen Chen; Hui Zhang (Food Hydrocolloids for Health)
Despite extensive research on protein-based nanoparticles for nutrient delivery, the structural features that govern bile salt interactions and subsequently enhance intestinal absorption and metabolic transformation remain insufficiently clarified. In this study, soy protein isolate nanoparticles enzymatically modified by Alcalase, Neutrase, and Flavorzyme (SPIH-A@NP, SPIHN@NP, SPIH-F@NP) were constructed as structural models to explore the relationship between nanoparticle interfacial properties, bile salt adsorption, and nutrient transport efficiency, using simulated gastrointestinal digestion and Caco-2/HT29 co-culture models. Compared with undigested nanoparticles and free β-carotene, digested nanoparticles exhibited significantly improved cellular uptake and transport efficiencies. Among them, SPIHN@NP and SPIH-F@NP retained more hydrophobic peptides and acidic subunits from 11S globulin, which enhanced bile salt adsorption, maintained smaller particle sizes post-digestion, and facilitated more efficient delivery of β-carotene and its metabolites. Additionally, the digestion process altered uptake pathways, with macropinocytosis contributing more prominently post-digestion. These findings provide mechanistic insight into structure–function relationships that can guide the rational design of protein-based nanocarriers for targeted absorption and metabolic modulation of lipophilic nutrients.